2001
DOI: 10.1074/jbc.m105648200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Caspase-9 Substrate and Detection of Its Cleavage in Programmed Cell Death during Mouse Development

Abstract: The caspase family of proteases represents the main machinery by which apoptosis occurs. In vitro studies have revealed that upstream caspases are activated in response to apoptotic stimuli, and the active caspases in turn process downstream effector caspases that are involved in the destruction of cellular structure. Caspase-9 is an upstream caspase that can become active in response to cellular damage, including deprivation of growth factors and exposure to oxidative stress in vitro. Little is known, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 47 publications
4
68
0
2
Order By: Relevance
“…The alternative pathway cannot be attributed to caspase-7, because the inhibitor DEVD also blocks this caspase (83). Caspase-9 substrates other than effector caspases-3 and -7 have already been described, such as vimentin (84). Activated caspase-9 was also found within the nucleus of dying cells, raising the possibility of additional nuclear substrates (85).…”
Section: Caspase-9 Induces An Alternative Pathway Of Cell Death Inmentioning
confidence: 97%
“…The alternative pathway cannot be attributed to caspase-7, because the inhibitor DEVD also blocks this caspase (83). Caspase-9 substrates other than effector caspases-3 and -7 have already been described, such as vimentin (84). Activated caspase-9 was also found within the nucleus of dying cells, raising the possibility of additional nuclear substrates (85).…”
Section: Caspase-9 Induces An Alternative Pathway Of Cell Death Inmentioning
confidence: 97%
“…The predominant death mechanism in the interdigits is apoptosis (Garcia-Martinez et al, 1993), but syndactyly is never observed by blocking a single molecular component of the apoptotic machinery.Consistent, with the apoptotic nature of cell death, numerous caspases (cysteineaspartic proteases), including initiator (caspase2, caspase 8, and caspase 9) and executioner caspases (caspase 3, caspase 6 and caspase 7; Fig. 2) are upregulated in the regressing interdigits (Nakanishi et al, 2001;Zuzarte-Luis et al, 2006), but interdigital cell death is not blocked in mice bearing single or compound caspase mutations, or deficient in caspase-activating adaptor protein, APAF-1 (Lakhani et al, 2006;Chautan et al, 1999;Kuida et al, 1998;Wang and Lenardo 2000;Nagasaka et al, 2009). It has been proposed that this apparent discrepancy is because interdigital mesenchyme die by necrosis if the apoptotic pathway is disrupted (Chautan et al, 1999).…”
Section: Molecular Machinery Of Cell Deathmentioning
confidence: 59%
“…At present, ÏŸ400 direct substrates of caspase-3 have been identified (LĂŒthi and Martin, 2007). However, only a few proteins have been reported to be substrates for caspase-9, including vimentin and amyloid ␀-protein precursor (APP) (Lu et al, 2000;Nakanishi et al, 2001). Here we found that antiSema7A staining is a valuable method for the sensitive detection of caspase-9 activity in tissue.…”
Section: Discussionmentioning
confidence: 99%